Research on the Reproduction of Trichogramma chilonis Based on Samia cynthia ricini Eggs: Temperature, Functional Response and Proportional Effect - Xi Yuan; Dunsong Li; Weili Deng (Insects)
T. chilonis is a commonly used biological agent, but its existing host eggs have shown some problems in the breeding of T. chilonis, and the search for more suitable host eggs is imminent. Here, we focused on S. c. ricini, an intermediate host that was used in the past for Trichogramma spp. but has since received less attention. We attempted to understand the effects of developmental temperature and duration on its longevity and egg production, evaluated the functional response of T. chilonis to S. c. ricini egg, and screened for a suitable wasp-to-egg ratio for the production of T. chilonis. Our results showed that the developmental temperature and duration after the emergence of T. chilonis significantly affected adult longevity and oviposition, that 25–28 °C is a suitable temperature range for the survival and e-g laying of S. c. ricini, and that a developmental duration of at least 24 h was required to obtain more qualified S. c. ricini eggs. T. chilonis demonstrated a type II functional response to S. c. ricini eggs; different wasp-to-egg ratios significantly affected the propagation efficiency of T. chilonis reproduction from S. c. ricini eggs, and the best reproduction efficiency was achieved with wasp-to-egg ratios of 1:2 and 1:3, Considering that there were no significant differences in most parameters between the two treatments, as well as cost concerns, we concluded that wasp-to-egg ratios of 1:2 are an important parameter that could be applied. Our results may provide some valuable insights into the mass rearing of T. chilonis.